2015
DOI: 10.1111/jocn.12972
|View full text |Cite
|
Sign up to set email alerts
|

Breathing exercise combined with cognitive behavioural intervention improves sleep quality and heart rate variability in major depression

Abstract: The cognitive behavioural intervention combined with a breathing relaxation exercise that included muscle relaxation, deep breathing and sleep hygiene could be provided with major depression during hospitalisation. Through group practice and experience sharing, participants could modulate their heart rate variability and share feeling about good sleep as well relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…14 Daily breathing exercises can reduce insomnia. 15 Chien et al, supported the hypothesis that the cognitive behavioral intervention combined with a breathing relaxation exercise could improve sleep quality and heart rate variability in patients with major depression 16 Although deep breathing exercises have an obvious impact on preventing further postoperative pulmonary problems in cardiac surgery, 17,18 few investigations have focused on the association between deep breathing exercise and sleep quality, 19 with almost no studies investigating the influence of deep breathing exercises on sleep duration and quality among patients undergoing coronary artery bypass graft during hospitalization. Therefore, this study set out to determine the effects of deep-breathing exercises on postoperative sleep duration and quality in patients undergoing coronary artery bypass graft (CABG).…”
Section: Introductionmentioning
confidence: 94%
“…14 Daily breathing exercises can reduce insomnia. 15 Chien et al, supported the hypothesis that the cognitive behavioral intervention combined with a breathing relaxation exercise could improve sleep quality and heart rate variability in patients with major depression 16 Although deep breathing exercises have an obvious impact on preventing further postoperative pulmonary problems in cardiac surgery, 17,18 few investigations have focused on the association between deep breathing exercise and sleep quality, 19 with almost no studies investigating the influence of deep breathing exercises on sleep duration and quality among patients undergoing coronary artery bypass graft during hospitalization. Therefore, this study set out to determine the effects of deep-breathing exercises on postoperative sleep duration and quality in patients undergoing coronary artery bypass graft (CABG).…”
Section: Introductionmentioning
confidence: 94%
“…Whilst there were too few studies reporting on selfperceived efficacy of self-care products and practices used for ID or IS (and none for SDB, RLS and other sleep disturbances) to form reliable generalizations, there was a significant level of satisfaction amongst participants for various types of self-care use including yoga, OTC medications (such as antihistamines and acetaminophen), relaxation and deep breathing. While research has shown deep breathing, relaxation and yoga exercises can help alleviate overall sleep quality (Sarris and Byrne 2011;Chien et al 2015;Orsal et al 2014) further research is required regarding the prevalence, safety and efficacy of self-care treatments such as OTC medications used frequently for sleep disturbances. ; safety concerns for antihistamines in particular have been highlighted (Goh et al 2009;Zhang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Slow, deep breathing actually helps the body override the sympathetic system which controls the fightor-flight response, and lets the parasympathetic system control the ability to relax (Pramanik et al, 2010). Another study by Chien et al (2015), conducted among clients with major depression, reported that cognitive behavioural intervention combined with a breathing relaxation exercise improved their sleep quality and heart rate variability. Though statistically not significant, there was marginal increment in attentional control in the control group.…”
Section: Discussionmentioning
confidence: 99%